Meningkatkan Pemahaman Siswa pada Mapel PKN Melalui Metode Diskusi di Kelas XI MAN 2 Tanah Datar - Zulhendri, Zulhendri (Inovan Publisher, 2025)
The Discussion method may be more suitable for teaching these manual skills, where physical movements and movements involved in holding an object will be learned, or for teaching routine matters (Staton, 1978:91). In other words, the Discussion method aims to teach physical skills rather than intellectual skills. Cardille argues that the discussion method can be used to: 1) teach students how to perform an action or use a new procedure or product, 2) increase students' confidence that a procedure is possible, 3) increase attention in learning and the use of procedures. By demonstrating or acting out an action, process, or procedure, the Discussion method has the following advantages: 1) It reduces the possibility of error compared to when students only read or hear explanations, because discussion provides a concrete picture that clarifies students' learning outcomes from their observations. 2) It allows students to be directly involved in discussion activities, thus providing a great opportunity for students to gain direct experience. The opportunity for student involvement gives students the chance to develop their skills and gain recognition and appreciation. 3) It makes it easier for students to focus their attention on things that are considered important, so that students will really pay special attention to these things.